Effects of predator call playbacks on reproductive success and extrapair paternity in blue tits. (September 2019) - Santema, Peter; Valcu, Mihai; Clinchy, Michael; Zanette, Liana Y.; Kempenaers, Bart
Abstract : An increase in the perceived risk of predation triggers many behavioural changes in prey species, which can have consequences for their reproductive success. Perceived predation risk may also influence investment in extrapair activities and, as a result, the frequency of extrapair paternity (EPP), but this possibility remains largely untested. Here we report on a study of a small passerine bird, the blue tit, Cyanistes caeruleus, in which we experimentally manipulated perceived predation risk by intermittently broadcasting predator calls throughout the breeding season. We found no evidence that the treatment affected two behavioural indices of extrapair activity (extrabox visits and the time of emergence from the nestbox in the morning during the fertile period) or the rate of EPP itself. The treatment also had no significant effect on clutch size, hatching success or most reproductive behaviours. However, nests in the predator playback treatment produced more fledglings, which was mainly due to a lower frequency of complete brood mortality. We discuss potential explanations for this finding, as well as for the lack of evidence for other effects of the predator playback treatment on blue tit reproductive behaviour. Several measures of reproductive performance suggest that the year in which the experiment took place was an unusually poor one and further work is therefore needed to assess the generality of our findings. Highlights: Perceived predation risk has been shown to affect breeding behaviour and success. Perceived predation risk may similarly affect extrapair behaviour and success. We played predator calls to a population of blue tits throughout the breeding period. We found no significant effects on breeding behaviour or extrapair activity/paternity. Nests exposed to predator calls had a lower incidence of complete brood mortality.